Evaluation of Serum Uric Acid as a Marker of Non-Alcoholic Fatty Liver Disease - Sadia Rehman; Fatima Mehboob; Nargis Anjum; Huma Salahuddin; Winay Kumar; Nosheen Wasee (KARACHI MEDICAL AND DENTAL COLLEGE, 2020)
Objective: The objective of this study is to evaluate the correlation of radiologically diagnosed non-alcoholic fatty liver disease (NAFLD) with serum uric acid (SUA) levels. Methods: It is a case control study conducted in private sector tertiary care hospital. A total of 200 subjects were involved in this study after calculation of sample size. The study participants were recruited from the medicine ward while the healthy controls were taken from the general population. Non probability consecutive sampling technique was employed. Inclusion criteria was patients who were diagnosed with fatty liver through abdominal ultrasonography. Exclusion criteria was patients suffering from any other chronic illness that can lead to an echogenic liver on ultrasound (viral hepatitis and diabetes) and history of alcohol consumption. Ethical approval for the study was taken from IRB. Data were entered and analysed using IBM SPSS version 23.0. Mean with standard deviation for age, BMI, SBP, DBP and SUA were reported between two study groups. Results: Highly significant results were observed between two groups; diseased and controls. Mean uric acid levels were found to be significantly higher in NAFLD (non-alcoholic fatty liver disease)cases as compared to controls, with serum uric acid showing an affirmative and positive linear relationship with fatty liver. An increase in BMI and systolic and diastolic blood pressures was also seen in NAFLD group as compared to controls which indicates that BMI is a comorbid for cardiac complications among the NAFLD patients. Conclusions: The study determined that uric acid levels elevate with progression of non-alcoholic fatty liver disease. This finding brings a new insight of uric acid in clinical practice. Increase in serum uric acid levels might serve as a trigger for physician to screen for NAFLD. An increase in BMI and systolic and diastolic blood pressure in NAFLD patients indicates underlying causes leading to cardiovascular complications in these patients.